Edukasi Manfaat Air Bersih Bagi Kesehatan di Desa Balane Dusun I Kecamatan Kinovaro, Kabupaten Sigi - Dinda Pratiwi; Katon Abdul Varid; Trisinta Trisinta; Wildawati Wildawati; Wirdayanti Wirdayanti; Yolin Meri Kristiani; Yordan Sesar; Afrina Januarista (CV. Multi Kreasi Media, 2023)
Clean water is one of the necessities that is used every day, therefore the quality of the water used must be clean, odorless and colorless. Because if you consume dirty water can cause various diseases such as diarrhea and skin diseases. Clean water can also be used as an effort to improve health status. By using clean water, we can avoid diseases such as diarrhea, cholera, dysentery, typhus, intestinal worms, skin diseases and poisoning. For this reason, it is mandatory for all family members to use clean water every day and maintain clean water quality in their environment. Based on observations made in the village of Balane, the use of cloudy water for daily consumption is due to a lack of knowledge about clean water and how to manage it, making this the objective of counseling on clean water management. This activity was carried out in the village of Balane Dusun I, Kinovaro District, Sigi Regency. The educational method used is lectures and the counseling media used is leaflets. The results of the counseling carried out are community knowledge regarding the importance of using clean water, managing clean water and the benefits of using clean water for health. Providing this counseling is a strategy to remind people of understanding and also increase public awareness of the importance of clean water for health in everyday life